A Teacher’s Beliefs and Practices of Using Video to Teach Speaking: A Case Study At SMA As-Salam Surakarta - Ummy Khoirunisya' Masyhudianti; Hanita Masithoh; Khoirun nisa (Universitas Islam Negeri Walisongo Semarang, 2018)
In the 21st century era, the implementation of technology in the form of common digital media and resources has been applied by teachers in language teaching and learning process. One of the digital media broadly used in teaching is video. It provides many advantages to promoteand improve students' speaking skill. This study aims to investigate the teacher's beliefs and the practices of using video in teaching speaking at the Ten Grade of SMA As-Salam Surakarta. A qualitative method was employed as the design of this study. An English teacher voluntarily involved as the participant. The data were collected through in depth-interview. The findings were categorized into three majors: 1) Teacher's belief in teaching speaking using video; 2) The reflection of those beliefs in classroom practices; 3) Factors shaping the teacher's beliefs and the practices. The result showed that there is no discrepancy between the teacher's beliefs and teaching practices. This study has a contribution to the development of English foreign language teaching. Hence, it is suggested that the English teacher should highlight their beliefs in order to create effective teaching practices.